2001
DOI: 10.22358/jafs/70017/2001
|View full text |Cite
|
Sign up to set email alerts
|

Fibre components negatively affect ileal protein digestibility in pigs

Abstract: The composition and properties of different NSP fractions of grain legumes, cereals and rapeseed meal are described and their implications in ileal digestibility of protein and amino acids in pigs are discussed. The effects of exogenous carbohydrases added to the diets of young pigs on protein digestibility are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Replacing part of the wheat with R also decreased the ileal digestibility of protein and AA, however, to a smaller extent than P. The lower ileal digestibility of R than wheat protein is in agreement with data reported by Buraczewska (2001), who also indicated that the AiD of R protein is related to the soluble dietary fibre content and viscosity of this cereal.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Replacing part of the wheat with R also decreased the ileal digestibility of protein and AA, however, to a smaller extent than P. The lower ileal digestibility of R than wheat protein is in agreement with data reported by Buraczewska (2001), who also indicated that the AiD of R protein is related to the soluble dietary fibre content and viscosity of this cereal.…”
Section: Discussionsupporting
confidence: 91%
“…The main components of rye and wheat NSP are arabinoxylans (pentosans) that constitute about 10% of dry matter in rye and 5.7 to 8.2% in wheat. Soluble NSP, in particular when provided in purified forms, increase digesta viscosity leading to slower absorption of amino acids (AA) and their lower ileal digestibility (Buraczewska, 2001;Wenk, 2001). Insoluble NSP reduce the transit time of digesta and are slowly degradable by the microflora in the large intestine (Buraczewska, 2001;Wenk, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of fibre added to the diet, as was the case in our study, depends on its physicochemical properties such as water-solubility, water-binding and viscosity which influence viscosity, dry matter content and transit time of digesta (Buraczewska, 2001). Cellulose is a water-insoluble fibre which does not affect ileal digestibility of protein and amino acids even when added up to the 13% level (Li et al, 1994) while inclusion of the soluble fibre (pectin) generally increases viscosity of digesta and decreases ileal digestibility (Mosenthin et al, 1993).…”
Section: Concentration Of Protein and Lipid Metabolites In Blood (Expmentioning
confidence: 64%
“…Slower average growth rate of the F 2 pigs resulted from the lowest protein digestibility of GM 20 diet caused by fibre components (Buraczewska, 2001) as well as lower metabolizable energy content (Skiba et al, 2005). In consequence these pigs consumed significantly lower amount of digestible protein and energy as compared with the control animals.…”
Section: Discussionmentioning
confidence: 98%